Active esophageal cooling during radiofrequency ablation of the left atrium: data review and update. (2nd December 2022) - Cooper, Julie; Joseph, Christopher; Zagrodzky, Jason; Woods, Christopher; Metzl, Mark; Turer, Robert W.; McDonald, Samuel A.; Kulstad, Erik; Daniels, James
ABSTRACT: Introduction: Radiofrequency (RF) ablation of the left atrium of the heart is increasingly used to treat atrial fibrillation (AF). Unfortunately, inadvertent thermal injury to the esophagus can occur during this procedure, potentially creating an atrioesophageal fistula (AEF) which is 80% fatal. The ensoETM (Attune Medical, Chicago, IL), is an esophageal cooling device that has been shown to reduce thermal injury to the esophagus during RF ablation. Areas covered: This review summarizes growing evidence related to active esophageal cooling during RF ablation for the treatment of AF. The review presents data demonstrating improved outcomes related to patient safety and procedural efficiency and suggests directions for future research. Expert opinion: The use of active esophageal cooling during RF ablation reduces esophageal injury, reduces or eliminates fluoroscopy requirements, reduces procedure duration and post-operative pain, and increases long-term freedom from arrhythmia. These effects in turn increase patient same-day discharge rates, decrease operator cognitive load, and reduce cost. These findings are likely to further accelerate the adoption of active esophageal cooling. Plain Language Summary: Atrial fibrillation is a condition in which the heart beats irregularly, causing symptoms such as palpitations, dizziness, shortness of breath, and chest pain. Atrial fibrillation increases the risk of stroke, heart failure, dementia, and death. One treatment for atrial fibrillation is a procedure called a catheter ablation. This procedure is minimally invasive and is performed by a specialized cardiologist, called an electrophysiologist. The electrophysiologist, or operator, uses an energy source, such as radiofrequency energy (radio waves), to stop erratic electrical signals from traveling through the heart. One complication of the catheter ablation is an inadvertent injury to the esophagus, the organ that passes food from the mouth to the stomach. If the injury is severe, it may develop into an atrioesophageal fistula, which often results in death. In this review, a new technology is described that helps prevent this type of injury and can provide additional benefits for the patient, operator, and hospital.